2019
DOI: 10.1002/agr.21628
|View full text |Cite
|
Sign up to set email alerts
|

Vertical coordination mechanisms and farm performance amongst smallholder rice farmers in northern Ghana

Abstract: Despite the fact that contracting facilitates farmer participation in agrifood value chains, evidence on farmers’ participation in different forms of contracts and the impact on farm performance is still limited. This study examines the determinants and impacts of vertical coordination mechanism‐spot market transactions, written, and verbal contract‐on‐farm performance of rice farmers in northern Ghana, using a multinomial BFG model to account for selectivity bias. The findings indicate that vertical coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…While this approach presents a potential risk of estimation error (Castrogiovanni, 1991), it presents methodologically lower risks than the commonly used measures of IOR performance: farm and/or household income, marketed output, and/or average price (Abdul-Rahaman and Abdulai, 2019;Alemu et al, 2016;Camanzi et al, 2018;Hobbs, 1995).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…While this approach presents a potential risk of estimation error (Castrogiovanni, 1991), it presents methodologically lower risks than the commonly used measures of IOR performance: farm and/or household income, marketed output, and/or average price (Abdul-Rahaman and Abdulai, 2019;Alemu et al, 2016;Camanzi et al, 2018;Hobbs, 1995).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Governance dichotomizes IOR into formal and informal relationships. Formal relationships typically involve written documents detailing participants' responsibilities and commitments to the relationship, while informal relationships generally involve verbal agreements, where participants' words are accepted as their bond (Abdul-Rahaman and Abdulai, 2019;Poku et al, 2018). Structure focuses on the channels used for constructing the relationship.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors such as education, availability of markets and other infrastructure, household access to credit, income and capital have been reported as influencing smallholders' decisions to participate in nonfarm work or economic diversification, since the lack of access to these factors appears to make it difficult for smallholders in many developing countries to diversify away from subsistence agriculture (Abdulai and CroleRees 2001; Wiggins et al 2011). Also, studies have shown that transaction costs, wealth and assets, and contractual and cooperative marketing substantially affect smallholders' marketing decisions and the quantities of inputs and outputs traded (Abdulai and Birachi 2008; Zanello 2012; Abdul‐Rahaman and Abdulai 2020). In particular, recent studies show that smallholder contract and cooperative marketing tend to reduce market risks; increase smallholders' bargaining power; and contribute to increasing farm productivity, income, and household welfare in some Asian and African countries (Abdulai and Birachi 2008;Ma, Abdulai, and Goetz 2018; Abdul‐Rahaman and Abdulai 2020).…”
Section: Food Security In Africamentioning
confidence: 99%